Synthesis and evaluation of novel analogues of mangiferin as potent antipyretic - Kant Singh S.; Sinha S.K.; Prasad S.K.; Kumar R.; Bithu B.S.; Sadish Kumar S.; Singh P. (My University, 2025)
Objective: To screen different analogues of mangiferin pharmacologically for antipyretic activity. Methods: The naturally occurring xanthone glycoside mangiferin was isolated by column chromatography from the ethanolic extract of stem bark of Mangifera indica. Mangiferin was further converted to 5-(N-phenylamino methyleno) mangiferin, 5-(N-p-chlorophenylamino methyleno) mangiferin, 5-(N-2-methyl phenylamino methyleno) mangiferin, 5-(N-p-methoxy phenylamino methyleno) mangiferin, 5-(N, N-diphenylamino methyleno) mangiferin, 5-(N-α-napthylamino methyleno) mangiferin and 5-(N-4-methyl phenylamino methyleno) mangiferin analogues. The synthesized compounds were further screened for antipyretic activity along with mangiferin at a dose level of 100 and 200 mg/kg. Mangiferin and its analogues were characterized by melting point andR fvalue determination and through spectral technique like UV, IR, and NMR spectral analysis. Results: The antipyretic activity of mangiferin as well as all analogues was found to be more significant in at higher dose ie. 200 mg/kg which was depicted through a decrease in rectal temperature up to 3 h. Conclusions: The antipyretic activity of mangiferin and its analogues may be attributed to inhibition in synthesis of TNF-α and anti-oxidant activity associated with amelioration of inflammatory actions of cytokines. © 2011 Hainan Medical College.